Increased risk for mental illness, injuries, and violence in children born to mothers with intellectual disability: A register study in Sweden during 1999–2012. (March 2017) - Wickström, Maria; Höglund, Berit; Larsson, Margareta; Lundgren, Maria
Abstract: Several studies have demonstrated that mothers with intellectual disability (ID) have a higher prevalence of mental health illness, lower socio-economic status, and a higher risk of alcohol and drug use compared to mothers without ID. The children of mothers with ID are over-represented in child protection and legal proceedings but are generally a less studied group than the mothers. The aim of this study was to investigate if children born to mothers with ID had an increased risk of being diagnosed with mental illness, injuries, and violence compared with children of mothers without ID. The study comprised a population-based cohort of children born in Sweden between 1999 and 2005. Data were collected from the Medical Birth Register and linked with two other national registers; ICD-10 codes were used for medical diagnoses, including ID. The children were followed from birth to seven years of age. In total, 478, 577 children were included, of whom 2749 were born to mothers with ID. Children of mothers with ID were at a greater risk of having mental health problems (adjusted odds ratio (OR) = 2.02; 95% confidence interval (CI) = 1.74–2.35) and ID (OR = 4.14; CI = 2.95–5.82) in early childhood. They had an increased risk for injuries due to falls (OR = 1.15; Cl 1.04–1.27). The largest risk related to trauma was violence and child abuse (OR = 3.11; CI = 1.89–5.12). In conclusion, children of mothers with ID had an increased risk for injuries, violence, and child abuse. We therefore suggest that parents with ID should receive evidence based support so that their children receive the best care and protection.